HUBUNGAN GANGGUAN PSIKIS KORBAN SCHOOL BULLYING SECARA VERBAL TERHADAP PRESTASI BELAJAR PESERTA DIDIK DI SMA NEGERI 4 TUBAN - Nafifin, Nadia; Raden Roro Nanik Setyowati (Universitas Negeri Surabaya (Unesa), 2024)
School bullying is an act of deviant violence committed within the school scope. One form of school bullying that often occurs is verbal bullying, where participants are victimized by harsh words, insults or threats that can harm the victim's psyche. School bullying verbally not only damages the psychological well-being of students but also threatens their academic impairment. The purpose of this study is to determine the relationship between the psychological disorders of verbal school bullying victims and the learning achievement of students at State Senior High School 4 Tuban. The method used was cantitactic with a simple linear regression model, with a sample used as many as 258 students in class X of State Senior High School 4 Tuban. The results obtained were that there was an influence between the psychological disorders of verbal school bullying victims on the learning achievement of students at SMA Negeri 4 Tuban, with the results of the hypothesis test (t-test) showing that the t count > t table, namely tcount > t table, which is 2.443 > 1.661771 with a significance value of 0.016 < 0.05, then this is accepted. From the results of the R Square test, it has a value of 0.062, which means that both variables, namely psychological disorders of victims of verbal school bullying, have an influence on the results of students' learning achievements. For further research, it can be done using different variables.